Multifunctional superamphiphobic fabrics with asymmetric wettability for one-way fluid transport and templated patterning - Liu, Hui (2017)
In this work, multifunctional superamphiphobic fabrics with special wettability were constructed by a facile dip-coating or electrospraying process using easily available materials, viz. silica nanoparticles, heptadecafluorononanoic, and fluoroalkyl silane. The obtained HFA–FAS–SiO2 NPs@surface exhibited a contact angle (CA) of 166.4 ± 3.7° and 155.9 ± 2.1° to water and hexadecane, respectively. In addition, this surface also showed stable repellency toward various corrosive droplets at a wide range of pH values, including HCl (pH = 1), NaCl (pH = 7), and NaOH (pH = 14) solutions. After immersion in the strong acid and base solutions for 24 h, the cotton surface still maintained excellent anti-wetting property. The surface was durable enough to withstand 120 cycles of abrasion and 5 cycles of accelerated standard laundry and still kept a water CA higher than 140° and an oil CA higher than 120°. Another treatment method adopted in this work, electrospraying has been proved to be able to realize asymmetric wetting with one side displaying highly anti-wetting behavior and the other side retaining the inherent hydrophilic and oleophilic nature of the pristine cotton fabric. Based on this special wettability, the obtained fabric could display a one-way directional transport feature. This method can also be extended to create hydrophilically and oleophilically patterned superamphiphobic cotton fabrics using a template. This novel fabric is useful for the development of intelligent cellulose-based substrates for various applications.